Effectiveness of Music to Improve Anxiety in Hemodialysis Patients: A Systematic Review and Meta-analysis. Issue 6 (November 2020) - Burrai, Francesco; Forton Magavern, Emma; Micheluzzi, Valentina; Magnaghi, Cristiano; Apuzzo, Luigi; Brioni, Elena
Abstract : Anxiety affects many hemodialysis patients. The response to treatment varies and often requires patients to take therapeutics for long periods; thus, many patients look for complementary approaches. There have been reports of music alleviating anxiety in hemodialysis patients. However, the efficacy of music needs to be evaluated. The objective of this study was to conduct a systematic review and meta-analysis to compare the effects of participation in standard care combined with music with standard care alone. This was a systematic review and meta-analysis of randomized controlled trials to determine the efficacy of music to lower anxiety in hemodialysis patients. Five studies were included in the review (290 patients). Listening to music resulted, on average, in an anxiety reduction that was −0.52 standard deviation units greater (95% confidence interval, −1.02 to −0.03 lower, P = .003) than in the standard care group. No adverse events were identified. All trials contained a risk of bias due to lack of blinding. The heterogeneity showed an I 2 = 75%. The strength of evidence was very low. No adverse events were identified. Few trials were available for inclusion, with small sample sizes and significant heterogeneity. Within these considerable limitations there was a demonstrated decrease in anxiety for hemodialysis patients receiving standard care augmented with music. The effect size was moderate. Results were inconsistent across studies. We are uncertain about the estimate. The likelihood that effect will be substantially different is very high. Further research has a large potential for reducing uncertainty about the effects of the music interventions.